Pengaruh Komunikasi Interpersonal dan Motivasi Kerja terhadap Kepuasan Kerja Guru SMK Swasta di Jakarta Timur - Lilik Chudaifah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
We rely on the capabilities of human resources in this globalization era. Vocational education graduates are expected to become productive individuals who are able to become intermediate workers and have readiness to face job competition. As the spearhead, teachers have a very important role, human resource management, it is necessary to link organizational strategy and human resources. When a person feels satisfaction at work, he will do everything possible to the best of his ability to complete his job assignments. Communication plays a very important role. Humans have social needs, which can be met through interpersonal communication. Interpersonal communication is useful for smoothing the flow of communication, both between superiors and subordinates vertically and fellow workers horizontally. Work motivation has an important and very basic role in the implementation of public service tasks that will accelerate the achievement of organizational goals. This research uses a quantitative approach, survey descriptive method. The population of this study were private vocational high school teachers in East Jakarta. The data description in this section includes data on variable Y (Job Satisfaction) as the final endogenous variable, variable X1 (Interpersonal Communication) as an exsogenous variable and variable X2 (Work Motivation) as an intermediate endogenous variable. The description of each variable is presented successively starting from the variables Y, X1, and X2. The results of hypothesis testing can be concluded that there is a positive direct effect of interpersonal communication and work motivation on job satisfaction with a correlation coefficient of 0.767 and a value of Fcount (105.214)> Ftable (3.06). So that interpersonal communication and work motivation have a positive direct effect on job satisfaction. Interpersonal communication and work motivation resulted in an increase in job satisfaction for private vocational high school teachers in the East Jakarta Region.